2008
DOI: 10.1021/nl8022143
|View full text |Cite
|
Sign up to set email alerts
|

Peeling Single-Stranded DNA from Graphite Surface to Determine Oligonucleotide Binding Energy by Force Spectroscopy

Abstract: We measured the force required to peel single-stranded DNA molecules from single-crystal graphite using chemical force microscopy. Force traces during retraction of a tip chemically modified with oligonucleotides displayed characteristic plateaus with abrupt force jumps, which we interpreted as a steady state peeling process punctuated by complete detachment of one or more molecules. We were able to differentiate between bases in pyrimidine homopolymers -peeling forces were 85.3 ±4.7 pN for polythymine and 60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
232
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(251 citation statements)
references
References 46 publications
17
232
2
Order By: Relevance
“…31 Previous work has focused on characterization of the adsorption of single nucleotides or nucleosides by atomic force microscopy (AFM), 32 isothermal titration calorimetry, 33 and theoretical calculations. [34][35][36] It was concluded that non-electrostatic interactions dominate the binding, 32 and the purine bases bind more strongly than the pyrimidines. 33,35,36 The adsorption of DNA on carbon nanotubes has also been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Previous work has focused on characterization of the adsorption of single nucleotides or nucleosides by atomic force microscopy (AFM), 32 isothermal titration calorimetry, 33 and theoretical calculations. [34][35][36] It was concluded that non-electrostatic interactions dominate the binding, 32 and the purine bases bind more strongly than the pyrimidines. 33,35,36 The adsorption of DNA on carbon nanotubes has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…33,35,36 The adsorption of DNA on carbon nanotubes has also been studied. [37][38][39][40][41][42][43] GO and nanotubes, however, are fundamentally different and the adsorption/desorption of oligonucleotides on GO have not been systematically tested as a function of solution conditions. We believe such studies can serve as a basis for further design and optimization of GO and DNA-based biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…21 Fundamental studies on the interaction between DNA and GO were also carried out. 11,[22][23][24][25][26][27][28][29][30][31][32] GO is a loosely defined material, and the oxygen content can vary quite a lot depending on the preparation condition. The adsorption affinity of DNA is likely to depend on the oxygen content.…”
Section: Introductionmentioning
confidence: 99%
“…The attractive forces between DNA and GO include - stacking, hydrophobic interaction, hydrogen bonding and van der Waals force. [3][4][5] Without a covalent linkage, 6 DNA adsorption is reversible. For example, adsorbed DNA can be desorbed by adding its complementary DNA (cDNA) to form a duplex.…”
Section: Introductionmentioning
confidence: 99%